Navigating the Mucosal Frontier: Mucus-penetrating Nanocarriers for Precision Pulmonary Drug Delivery and Respiratory Therapeutics - Pranav Sisodia; Shikha Baghel Chauhan; Chirag Jain (Current Respiratory Medicine Reviews, 2026)
This review article focuses on the potential of Mucus-Penetrating Nanocarriers (MPNs) in overcoming biological barriers in oral and pulmonary drug delivery systems. The mucus barrier, composed mostly of mucin glycoproteins, acts as a biological barrier, trapping conventional drug delivery systems, thus leading to rapid clearance. To overcome this, MPNs have been designed to have optimal size, surface charge, and hydrophilic coatings, such as polyethylene glycol (PEG), thereby facilitating the diffusion of the nanocarriers through the mucus barrier without interference with adhesion. The article also compares the characteristics of the mucus barrier in the gastrointestinal tract and the lungs, highlighting their structural differences. The article also focuses on the physicochemical characteristics such as the size, morphology, surface characteristics, and stability of the nanoparticles, thus discussing the various formulation methods for the nanoparticles, including the use of polymeric, lipid, and hybrid nanoparticles, thus highlighting the shift from the conventional mucoadhesive approach to the MPNs approach, thus enhancing the efficacy of the drug delivery system. The safety, immunogenicity, and current regulatory status have also been addressed. Developments, such as stimuli-responsive nanocarriers and artificial intelligence, are discussed as potential areas of future directions. In conclusion, the use of MPNs is a promising approach for enhancing drug delivery across mucosal membranes, and further research is needed.